FORMULATION AND PRODUCTION TECHNOLOGY OF BREAD WITH KELP, AMARANTH, OAT AND RICE FLOUR - G. A. Hamatgaleeva (Современная наука и инновации, 2022)
The article presents the results of a study of consumer properties of bread using a functional ingredient - kelp fine grinding, as well as amaranth, oats and rice flour. The addition of kelp fine grinding, amaranth, rice and oat flour in bread recipe helps to prevent iodine deficiency disorders, reduces the level of cholesterol in the blood, stimulates the human heart, and others. The results prove that the bread with the addition of kelp fine grinding, as well as oats, amaranth and rice flour is characterized by high nutritional value and lower cost compared with traditional bread from wheat flour baking premium